A strategy for generating alkyl radicals from aliphatic esters and lactones via sequential hydrolysis and photoinduced decarboxylation. Issue 13 (25th March 2015) - Saito, Hikaru; Kanetake, Takayuki; Osaka, Kazuyuki; Maeda, Kousuke; Morita, Toshio; Yoshimi, Yasuharu
Graphical abstract: Abstract: Sequential hydrolysis and photoinduced decarboxylation of methyl aliphatic esters lead to efficient generation of alkyl radicals under mild conditions. The generated alkyl radicals react with a variety of reagents to produce addition, reduction, and substitution products. In addition, the new tin and halogen free process for alkyl radical generation is applicable to a variety of aliphatic esters including those of dipeptides, steroids, saccharides, and lactones.